Negotiating Governance on Non-Traditional Security in Southeast Asia and Beyond - Anthony, Mely Caballero (Columbia University Press, 2019)
The threats the world currently faces extend beyond traditional problems such as major power competition, interstate conflict, and nuclear proliferation. Non-traditional security challenges such as climate change, migration, and natural disasters surpass states' capacity to address them. These limitations have led to the proliferation of other actors-regional and international organizations, transnational networks, local and international nongovernmental organizations-that fill the gaps when states' responses are lacking and provide security in places where there is none. In this book, Mely Caballero-Anthony examines how non-traditional security challenges have changed state behavior and security practices in Southeast Asia and the wider East Asia region. Referencing the wide range of transborder security threats confronting Asia today, she analyzes how non-state actors are taking on the roles of "security governors," engaging with states, regional organizations, and institutional frameworks to address multifaceted problems. From controlling the spread of pandemics and transboundary pollution, to managing irregular migration and providing relief and assistance during humanitarian crises, Caballero-Anthony explains how and why non-state actors have become crucial across multiple levels-local, national, and regional-and how they are challenging regional norms and reshaping security governance. Combining theoretical discussions on securitization and governance with a detailed and policy-oriented analysis of important recent developments, Negotiating Governance on Non-Traditional Security in Southeast Asia and Beyond points us toward "state-plus" governance, where a multiplicity of actors form the building blocks for multilateral cooperative security processes to meet future global challenges.